Comparison of 3 Methodologies for Genotyping of Small Deletion and Insertion Polymorphisms. (6th January 2020) - Goh, Su Kah; Musafer, Ashan; Witkowski, Tom; Muralidharan, Vijayaragavan; Christophi, Christopher; Do, Hongdo; Dobrovic, Alexander
Abstract: BACKGROUND: The quantification of genomic chimerism is increasingly recognized for its clinical significance after transplantation. Before the measurement of chimerism, accurate genotyping of genetic polymorphisms for informative alleles that can distinguish donor DNA from recipient DNA is essential. The ease of allelic discrimination of small deletion and insertion polymorphisms (DIPs) makes DIPs attractive markers to track chimerism. Current methodologies for the genotyping of DIPs are largely based on "open-tube" approaches. "Closed-tube" approaches involving no or minimal post-PCR handling are preferred. We compared 3 distinct methodologies to determine an optimal platform for DIP genotyping. METHODS: Genomic DNA from 19 normal individuals was genotyped for 6 small biallelic DIPs using high-resolution melting analysis (HRMA), probe-free droplet digital PCR (ddPCR), and microfluidic electrophoresis of PCR products. For HRMA, 3 different platforms were compared. RESULTS: Our newly developed probe-free ddPCR approach allowed the genotype of each DIP to be determined by fluorescence intensity based on amplicon size. Microfluidic electrophoresis also allowed genotypes to be determined by amplicon size. HRMA assays allowed the genotype of each DIP to be determined by melting profile. Genotyping results were concordant between the 3 methodologies. HRMA was the most readily performed methodology and was robust across 3 separate HRMA-capable platforms. CONCLUSIONS: We demonstrated the effectiveness of probe-free ddPCR to accurately genotype small biallelic DIPs. Nevertheless, HRMA proved to be the optimal approach for genotyping small DIPs because closed-tube approaches are preferred owing to rapid and less laborious workflows and least risk of PCR contamination.